Free style perforator based propeller flaps: Simple solutions for upper extremity reconstruction! - Nikhil Panse; Parag Sahasrabudhe (Indian Journal of Plastic Surgery)
Background: The introduction of perforator flaps by Koshima et al. was met with much animosity in the plastic surgery fraternity. The safety concerns of these flaps following the intentional twist of the perforators have prevented widespread adoption of this technique. Use of perforator based propeller flaps in the lower extremity is gradually on the rise, but their use in upper extremity reconstruction is infrequently reported, especially in the Indian subcontinent. Materials and Methods: We present a retrospective series of 63 free style perforator flaps used for soft tissue reconstruction of the upper extremity from November 2008 to June 2013. Flaps were performed by a single surgeon for various locations and indications over the upper extremity. Patient demographics, surgical indication, defect features, complications and clinical outcome are evaluated and presented as an uncontrolled case series. Results: 63 free style perforator based propeller flaps were used for soft tissue reconstruction of 62 patients for the upper extremity from November 2008 to June 2013. Of the 63 flaps, 31 flaps were performed for trauma, 30 for post burn sequel, and two for post snake bite defects. We encountered flap necrosis in 8 flaps, of which there was complete necrosis in 4 flaps, and partial necrosis in four flaps. Of these 8 flaps, 7 needed a secondary procedure, and one healed secondarily. Although we had a failure rate of 12-13%, most of our failures were in the early part of the series indicative of a learning curve associated with the flap. Conclusion: Free style perforator based propeller flaps are a reliable option for coverage of small to moderate sized defects. Level of Evidence: Therapeutic IV.